The Contribution of Women Rubber Farmers in Improving the Family Economy According to Sharia Economic Perspective (Case Study of Sereka Babat Toman Village) - Puteri Sulba Alrahim; Mahmud Alfan Jamil; Lemiyana (Universitas Muhammadiyah Palu, 2025)
Many women at this time have contributed to meeting the needs of the household. Various fields of work have been taken over, not only working in the office, even women are also willing to work in the field to become sales promotion girls, and some are even willing to become rubber farmers. This is done to help their husbands in meeting the needs of life. This study aims to find out and analyze the contribution of women rubber farmers in improving the family economy in Sereka Village, to find out how the view of sharia economics towards women rubber farmers in improving the family economy in Sereka Village, and to find out the obstacles of women rubber farmers in improving the family economy in Sereka Village. The type of research used is qualitative research, with data collection techniques using interviews, and documentation with the number of research informants as many as 15 female rubber farmers consisting of farmers and managers in Sereka Village, Babat Toman District. The data analysis techniques used are in the form of data reduction, data presentation, and conclusions. Based on the results of research and discussion, the results were obtained that the contribution of women rubber farmers was 22%. The contributions provided provide benefits for meeting basic needs, children's education, family health, savings, recreation, home repairs. According to Islamic views, female rubber farmers in Sereka Village, Babat Toman District are allowed as long as it is in accordance with Islamic law. Obstacles received by women rubber farmers in Sereka Village, Babat Toman District, such as price, weather, ability, plantation management, diseases, plantation locations and infrastructure